(untitled) - Burns, Tom (London, 2016)
Practical and interactive, this edition features three brand new chapters to arm you with even more essential skills including how to produce a dissertation, planning your career and focussing on building relationships with lecturers and other students to help you get ahead.
Keywords: Kỹ năng học tập,Study skills; Sổ tay, sách hướng dẫn, v.v.,Handbooks, manuals, etc